A numerical solution of the sine-Gordon equation using the modified decomposition method - Kaya, D (Elsevier Science Inc, 2003)
The decomposition method for solving the sine-Gordon equation has been implemented. By using a number of initial values, the explicit and numerical solutions of the equation are calculated in the form of convergent power series with easily computable components. The present method performs extremely well in terms of accuracy, efficiency, simplicity, stability and reliability. (C) 2002 Elsevier Science Inc. All rights reserved.
Keywords: the decomposition method; the modified decomposition method; nonlinear Klein-Gordon equations; the sine-Gordon equation